Perioperative management of patients receiving glucocorticoids in rheumatology - Kardaş, Rıza Can; Küçük, Hamit (Acta Medica, 2024)
Glucocorticoids are a cornerstone in the management of rheumatic diseases due to their potent anti-inflammatory and immunomodulatory effects. However, their perioperative use presents distinct challenges, including an elevated risk of infection, impaired wound healing, and the potential for glucocorticoid-induced adrenal insufficiency (GI-AI). This review examines the perioperative implications of glucocorticoid therapy, with a focus on infection risk, adrenal insufficiency, and recommendations from clinical practice guidelines. Evidence indicates a correlation between glucocorticoid use and increased perioperative complications, although the efficacy of dose reduction strategies in mitigating these risks remains uncertain. GI-AI, a common complication of prolonged glucocorticoid use, necessitates careful perioperative management to prevent adrenal crises. Guidelines from British, American, and German societies propose slightly differing approaches, albeit with low levels of evidence, emphasizing the importance of individualized patient care.